Combined Dextroamphetamine and Transcranial Direct Current Stimulation in Poststroke Aphasia - Keser, Zafer; Dehgan, Michelle Weber; Shadravan, Shaparak; Yozbatiran, Nuray; Maher, Lynn M; Francisco, Gerard E (American journal of physical medicine & rehabilitation, 2017)
There is a growing need for various effective adjunctive treatment options for speech recovery after stroke. A pharmacological agent combined with noninvasive brain stimulation has not been previously reported for poststroke aphasia recovery. In this "proof of concept" study, we aimed to test the safety of a combined intervention consisting of dextroamphetamine, transcranial direct current stimulation, and speech and language therapy in subjects with nonfluent aphasia. Ten subjects with chronic nonfluent aphasia underwent two experiments where they received dextroamphetamine or placebo along with transcranial direct current stimulation and speech and language therapy on two separate days. The Western Aphasia Battery-Revised was used to monitor changes in speech performance. No serious adverse events were observed. There was no significant increase in blood pressure with amphetamine or deterioration in speech and language performance. Western Aphasia Battery-Revised aphasia quotient and language quotient showed a statistically significant increase in the active experiment. Comparison of proportional changes of aphasia quotient and language quotient in active experiment with those in placebo experiment showed significant difference. We showed that the triple combination therapy is safe and implementable and seems to induce positive changes in speech and language performance in the patients with chronic nonfluent aphasia due to stroke.